1999
DOI: 10.1051/apido:19990405
|View full text |Cite
|
Sign up to set email alerts
|

Nestmate discrimination in the African stingless bee Hypotrigona gribodoi Magretti (Hymenoptera: Apidae)

Abstract: -Sociobiological studies of the highly eusocial stingless bees (Meliponinae)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 19 publications
(18 reference statements)
1
8
1
Order By: Relevance
“…Bees in the CCRI41 group consumed less pollen than control bees during the course of the assay and a similar pattern occurred for bees exposed to imidacloprid-contaminated pollen. The antifeedant effect in group exposed to imidacloprid-contaminated pollen was consistent with previous studies on honey bees (Kirchner 1999; Ramirez-Romero et al 2005; Ramirez-Romero et al 2008b) and on Homoptera (Nauen et al 1998a, b). The detection and uptake of nectar and pollen involves sophisticated nervous system activity which can be perturbed by the presence of chemical insecticide, whether that behaviour took place in the hive or outside (Desneux et al 2007).…”
Section: Discussionsupporting
confidence: 91%
“…Bees in the CCRI41 group consumed less pollen than control bees during the course of the assay and a similar pattern occurred for bees exposed to imidacloprid-contaminated pollen. The antifeedant effect in group exposed to imidacloprid-contaminated pollen was consistent with previous studies on honey bees (Kirchner 1999; Ramirez-Romero et al 2005; Ramirez-Romero et al 2008b) and on Homoptera (Nauen et al 1998a, b). The detection and uptake of nectar and pollen involves sophisticated nervous system activity which can be perturbed by the presence of chemical insecticide, whether that behaviour took place in the hive or outside (Desneux et al 2007).…”
Section: Discussionsupporting
confidence: 91%
“…Likewise, aggression was absent between colonies of different aggregations. This atypically peaceful behavior contrasts with other studies on stingless bees that found relatively strong aggression between con-or heterospecific non-nestmate individuals (Johnson and Hubbell, 1974;Johnson, 1977, 1978;Howard, 1985;Inoue et al, 1999;Kirchner and Friebe, 1999;Nunes et al, 2008;.…”
Section: Discussioncontrasting
confidence: 99%
“…Intraspecific conflict can only take place if bees discriminate nest mates from non-nest mates. Nest mate discrimination has been demonstrated in several Melipona (Breed and Page, 1991;Inoue et al, 1999) and Trigonine species (Suka and Inoue, 1993;Kirchner and Friebe, 1999) and seems common in stingless bees. Fights between non-nest mates usually end in the death of one or both of the bees (Breed and Page, 1991;Biesmeijer and Slaa, pers.…”
Section: In the Field: Information From Conspecific Non-nest Matesmentioning
confidence: 99%